Chronic bronchitis in West Sweden – a matter of smoking and social class. Issue 1 (1st January 2016) - Axelsson, Malin; Ekerljung, Linda; Eriksson, Jonas; Hagstad, Stig; Rönmark, Eva; Lötvall, Jan; Lundbäck, Bo
Abstract : Background: Although chronic bronchitis is associated with impaired quality of life, hospitalisations and increased mortality, it has been less in focus after the introduction of the term chronic obstructive pulmonary disease (COPD). There are no recent published data on the prevalence of chronic bronchitis from the Scandinavian countries. Aim: The main aim of the present study was to estimate the prevalence of chronic bronchitis in West Sweden by using data from a large-scale epidemiological study of the general population. A further aim was to identify current risk factors for chronic bronchitis in a population with a major decrease in the proportion of smokers. Methods: From the 18, 087 questionnaire responders out of 30, 000 invited to participate at the West Sweden Asthma Study, 2, 000 subjects were randomly selected and invited to detailed clinical examinations performed during 2009–2013. A total of 1, 172 subjects aged 17–79 participated in the examinations which included, among others, spirometry and structured interviews. Chronic bronchitis was defined according to reported symptoms. Results: The overall prevalence of chronic bronchitis was 7.2% (men 7.6%; women 6.8% ns), and it was 8.7% in subjects older than age 60. Chronic bronchitis was strongly associated with smoking, defined both as current smoking status and pack-years. Other risk factors were increasing age, low socio-economic class and urban living. Of those with chronic bronchitis, 22% fulfilled the GOLD criteria of COPD. Conclusion: The prevalence of chronic bronchitis was somewhat lower than found by studies in Sweden in the 1980s and the prevalence was now similar in men and women. Although smoking was still the dominating risk factor for chronic bronchitis, the relative importance of smoking had decreased parallel with a decreasing smoking prevalence, while the relative importance of other factors than smoking had increased compared to previous studies.